Individual Tire Mileage Measurement - Mohammad, Muhammad Syazwan (Universiti Teknologi PETRONAS, 2021)
Tire burst prevention is being actively researched as tire burst is the major factor in causing traffic accidents and consequently bring huge loss to the society. Automotive companies have long equipped complex sensory system which address varieties of car and its components maintenance issues. If an issue that could potentially affect user safety and environmental pollution, these sensing systems alert the user of these issues and he can have his vehicle checked. However, there is still no tire monitoring system that could tell the owner when a tire has passed its road-safe time or distance limit. Conventionally, car owner inspects their car tire’s life just by visual inspection and time-based method. These methods are unreliable as it based on personal whim and thus leads to the development of this project which is to develop tire monitoring system that can measure each individual tire’s mileage. We can now determine the absolute distance travelled of each tire and hence we can determine the exact time to replace each individual tire of a multi-tire vehicles This prototype is useful for all types of companies as it eases their work on maintaining their land fleets. IoT is introduced for this project so that every automobile owner can just monitor on their mobile phone or other devices. This project development has been narrowed down into three system which are measurement, monitoring and communication system.